EQUINOXE study: Impact of relational cohesion and sexuality on the quality of life of patients treated with gonadotropin‐releasing hormone agonist for prostate cancer. Issue 1 (19th October 2021) - Droupy, Stéphane; Colson, Marie‐Hélène; Pello‐Leprince‐Ringuet, Nathalie; Perrot, Valérie; Descazeaud, Aurélien
Abstract: Objectives: To measure the effect of dyadic adjustment on changes in patients' quality of life when initiating treatment with gonadotropin‐releasing hormone (GnRH) agonist. Patients and methods: A prospective, multicenter, longitudinal, and non‐interventional study (NCT02630641) that included patients with prostate cancer starting GnRH agonist therapy, and their partners, in 157 centers in France. Data were collected at inclusion and after 6 months of treatment on quality of life (WHOQOL‐BREF), disease perception (B‐IPQ), disease symptoms (QLQ‐PR25), and perception of cohesion within the couple (dyadic adjustment, DAS‐16). Results: The Full Analysis Set included 492 patients (median age [Q1;Q3]: 74 [68;80] years). An improvement of the quality of life (defined as the improvement of at least one of the four dimensions of WHOQOL‐BREF) was reported in 290/434 (67%) patients between baseline and follow‐up. Quality of life was better at baseline and follow‐up in patients with good cohesion within the couple than in those with medium or poor cohesion. Factors associated with improvement in quality of life of patients were the following: initial presence of QLQ‐PR25 hormonal treatment‐related symptoms (OR [95% CI]: 3.00 [1.46, 6.17]) suggesting testosterone deficiency symptoms at baseline and initial low level (2.04 [1.12, 3.72]) or absence of sexual activity (2.23 [1.11, 4.50]) before GnRH agonist initiation. Conclusion: Men with the greatest improvement in quality of life after initiating hormone therapy were those with, at baseline, testosterone deficiency symptoms (identified by QLQ‐PR25 treatment‐related symptoms score) or no/low sexual activity. Cohesion within the couple was not confirmed as an influence on the evolution of quality of life.